STUDI ANALISA SERANGAN SQL INJECTION - Nursapdahi, Nursapdahi; Fitrani, Arif Senja; Rosid, Mochamad Alfan; Aji, Sukma (Universitas Nusantara PGRI Kediri, 2022)
At this time the website has become one of the modern information media that is growing very quickly. In making a website, not only the design and information are important, but the security aspect of the website itself has a very important role in a website. The need for website security arises from the need to protect data. First, from data loss and corruption. Second, there are irresponsible parties who want to access and change data. Other problems include self-data protection, excessive delays when accessing or using data. The method used in this test will use tools in the form of software and certain methods used to test the security of a website. To analyze website security, the software used is Snort IDS (Intrusion Detection System) and Wireshark. SQL Injection is actually not a new thing in the world of hacking as a web hacking technique, SQL Injection can damage the database of a website. The technique used in SQL Injection is to input basic SQL commands such as create, insert, update, drop, alter, union and select along with other commands.